The use of reflective practice towards achieving effective English language teaching at primary schools - Siti Noor Aneeis Hashim; Nurahimah Mohd Yusoff (Institute of Advanced Engineering and Science, 2021)
The purpose of this study was to explore the use of reflective practice by English language teachers in providing effective English language teaching in primary school classrooms. This qualitative case study involving six in-service English language teachers who were selected based on purposive sampling. The data in this study were collected using teachers’ reflection logs and a series of semi-structured interviews with the English language teachers. Thematic analysis was used to identify emerging themes based on the codes gathered from the interviews and teachers’ reflections logs. The results showed that the English language teachers used reflective practice erstwhile in preparing and providing effective English language teaching for the students. They reviewed what has been accomplished and identify constructive guidelines to follow to succeed in the future teaching. They have also been doing variations of changes in teaching based on reflecting on the quality of instruction, levels of instruction, using incentive to motivate the students and managing time equally in teaching and learning process to help the children in learning English language. Since there is no clear guideline for teachers who use reflective practice in their classes, this study provided some insights on the preparations and the use of reflective practice as part of their teaching and learning process.